The Importance of Organisational Skills to Manage Women's Cooperatives - Mutiarni, Rita (KnE Social Sciences, 2022)
As one of the economic pillars of Indonesia, cooperatives are expected to be able to take on more roles to support the economy of Indonesia. However, in reality, the development of cooperatives in Indonesia is still lagging compared to other financial institutions. It is presumably because the management still follows a simple structure by relying on the ability of human resources, namely cooperative management. This study aimed to determine human capital and spiritual capital’s effect on women’s cooperatives’ performance in the Jombang district. This study used a quantitative approach. The sample used was 62 women’s cooperatives. The data was collected through questionnaires and various documents about women’s cooperatives in the Jombang district. The analytical tool used to test the hypothesis uses Warp Partial Least Square (Warp PLS) version 7.0. The results showed that there exists a direct influence between human and spiritual capital on the performance of women’s cooperatives in Jombang. Human capital has also been shown to influence the implementation of spiritual capital. Therefore, spiritual capital can also mediate the role of human capital in the performance of cooperatives in Jombang. The results of this study serve as a reference for stakeholders of women’s cooperatives in Jombang to provide guidance and training to managers of women’s cooperatives in Jombang, especially in the form of improving practical skills for daily cooperative management. Keywords: Human capital, spiritual capital, women’s cooperative performance, Jombang